PENINGKATAN KETERAMPILAN MENULIS CERITA ANAK MENGGUNAKAN MEDIA KARTU DIKELAS II SEKOLAH DASAR 29 SUNGAI AMBAWANG - Saputri, Indah Anggini; Halidjah, Siti; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is? whether by using the media card can be improve childrens?s story writing skills in grade II public elementary school 29 Sungai Ambawang? the purpose of this study is to improve child?s story writing skills using card media in cllas II primary school 29 Sungai Ambawang. The method used descriptive method, the form of reseach used is this classroom action research study is collaborative. Action activity done in class 2 primary school with research subject that is student of calss II which Sungai Ambawang amounted to 22 people of data collecting techninque used that is techninque of direct obsevation and measurement techninque, the results showed that the student?s writing skill in cycles I with I time meeting in each cycle the results obtained are I ability of teachers in designing learning in cyle (I) obtained average score of 3,28 cycle (II) obtained average score of 3,55. (III) the abillty of teachers to implement learning in cycle 3,69 (I) obtained an average score of 3,25. (II) obtained an average score of 3,42, cycle (III) earned an average score of 3,69, (I) students learning autcomes incycle I obtained an average of 72,72 in either category, cycle (II) obtained a mean of 81,81 in both excellent category and cyle (III) and obtained a mean of 92,72 in either category incan be concluded that by using media card card improve the writing skills of students in public elementary school II sungai ambawang. Keywords: Improvement, of card writing media skills